2012
DOI: 10.1148/radiol.12112520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multipeak Spectral Modeling of Fat for Liver Iron and Fat Quantification: Correlation of Biopsy with MR Imaging Results

Abstract: Purpose:To investigate the effect of the multipeak spectral modeling of fat on R2* values as measures of liver iron and on the quantification of liver fat fraction, with biopsy as the reference standard. Materials and Methods:Institutional review board approval and informed consent were obtained. Patients with liver disease (n = 95; 50 men, 45 women; mean age, 57.2 years 6 14.1 [standard deviation]) underwent a nontargeted liver biopsy, and 97 biopsy samples were reviewed for steatosis and iron grades. MR imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
181
6
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(203 citation statements)
references
References 47 publications
10
181
6
6
Order By: Relevance
“…In addition, both examinations showed high accuracy in the detection of clinically significant hepatic steatosis (AUC, 0.93), as well as the presence of hepatic fibrosis (AUC, 0.85). Our study results show good agreement with previous studies, which also demonstrated excellent accuracy in the estimation of hepatic FF by using multiecho chemicalshift imaging with multipeak fat spectrum modeling or T2-corrected multiecho single-voxel 1 H MR spectroscopy (39,40), as well as significant correlation between LS values at MR elastography and the degree of hepatic fibrosis at pathologic examination (25,41). Considering that both methods are achieved within a breath hold and cover a larger area than percutaneous liver biopsy, as well as the high accuracy in the prediction of substantial hepatic steatosis, MR fat quantification and MR elastography may serve as a screening tool for the selection of donors without a risk of substantial hepatic steatosis and/or hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, both examinations showed high accuracy in the detection of clinically significant hepatic steatosis (AUC, 0.93), as well as the presence of hepatic fibrosis (AUC, 0.85). Our study results show good agreement with previous studies, which also demonstrated excellent accuracy in the estimation of hepatic FF by using multiecho chemicalshift imaging with multipeak fat spectrum modeling or T2-corrected multiecho single-voxel 1 H MR spectroscopy (39,40), as well as significant correlation between LS values at MR elastography and the degree of hepatic fibrosis at pathologic examination (25,41). Considering that both methods are achieved within a breath hold and cover a larger area than percutaneous liver biopsy, as well as the high accuracy in the prediction of substantial hepatic steatosis, MR fat quantification and MR elastography may serve as a screening tool for the selection of donors without a risk of substantial hepatic steatosis and/or hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…Kühn et al (52) reported an MR imaging PDFF threshold of 4.5% for diagnosis of grade 1 or higher steatosis. This threshold provided 84% sensitivity and 100% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, iron grade was not available as part of our histologic analysis. Instead, we used R2* as a surrogate for iron to address its potential confounding effect on the relationship between steatosis and MR imaging PDFF (52).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the spectral characteristics of triglycerides between BAT and WAT are quite similar, with only subtle differences in chain length and degree of carbon unsaturation (40). Furthermore, several recent literature reports have shown that the estimated FF is minimally impacted by moderate differences in the fat spectral models assumed during water-fat decomposition and image reconstruction (41,42). The use of an appropriate multi-peak fat spectral model is nonetheless more accurate than the traditional single-peak water-methylene model.…”
Section: Discussionmentioning
confidence: 99%